Psychiatric clinics of North America : obesity and associated eating disorders: a guide for mental health professionals - Berkowitz, Robert I.; Bray, George A.; Brownell, Kelly D.; Butryn, Meghan L.; Catenacci, Victoria A.; Davis, Kelliann K.; Dililo, Vicki; Dumon, Kristoffel; Fabricatore, Anthony N.; Faulconbridge, Lucy F.; Foster, Gary D.; Hayes, Matthew R.; et al. (Philadelphia : W.B. Saunders Company, 2011)
The epidemic of obesity is well known to readers of this issue, as it is to just about anyone who reads a newspaper, watches television, or scrolls the internet. This edited issue jopins others in providing an overview etiology, consequences, prevention, and treatment of obesity in adults.
Obesity : overview of an epidemic -- Regulation of energy balance and body weight by the brain : a distributed system prone to disruption -- Obesity, psychiatric status and psychiatric medication -- Eating disorders and obesity -- Treatment of binge eating disorder -- Treatment of night eating syndrome -- Medical and behavioral evaluation of patients with obesity -- Dietary approaches to the treatment of obesity -- Obesity and physical activity -- Behavioral treatment of obesity -- Motivational interviewing for weight loss -- Drug treatment of obesity -- Surgical treatments for obesity -- Obesity : a public health approach
Includes index.
Keywords: EATING DISORDER -- PSYCHOLOGICAL ASPECTS; OBESITY -- PSYCHOLOGICAL ASPECTS